Postauricular Dermoid Cyst: A Case Report - Mohammad Bagher Raziee; Saadat Mirsadraee; Nazanin Oraee Nasooti; Armin Elahifar (مجله دانشکده پزشکی اصفهان, 2011)
Background: Dermoid cyst is one the most common developmental lesions in the embrioyonic period. The cyst can exist anywhere but commonly is seen in the midline of the body. One of the uncommon areas dermoie cysts are seen is temporal area (postauricular skin, the middle ear or, even rare on the Eustachian tube). Case Report: In this study, a rare case of a dermoid cyst located behind the ear with abnormal gradual growth in several years is reported.